Supportive oncology: a blueprint for patient-centric care - Tali, Tavseef Ahmad; Amin, Fiza (International Journal of Basic & Clinical Pharmacology, 2024)
The article emphasizes a paradigm shift toward patient-centric care while providing a thorough examination of the changing supportive oncology landscape. When a patient is diagnosed with cancer, they must not only deal with the medical effects of the illness but also manage difficult emotional, social, and practical issues. Understanding the critical role supportive care plays in improving cancer patients’ overall quality of life, this book explores the essential elements of a patient-centric approach. Evidence-based procedures, recommendations, and the incorporation of patient viewpoints are all included in the suggested blueprint for patient-centric oncology care. Healthcare professionals may improve cancer patients’ quality of life, foster resilience, and help create a more sympathetic and caring healthcare system by adopting an all-encompassing approach. In the end, the paper makes the case for the broad implementation of supportive oncology as a crucial part of cancer treatment, enabling patients to face their ordeal with dignity and resiliency.